AI LIMITI DEL DISCORSO: U-TOPOS, O L’ASSENZA DI LUOGO - Addis, Maria Cristina (CAUCE. Revista Internacional de Filología, Comunicación y sus Didácticas, 2019)
our paper focuses on the discourse expressed and shaped by Utopia, building on Louis Marin’s analysis of the novel by Thomas More. Aim of the paper is to point out a theoretical approach to the study of relationships between power, space and subjectivity which can consistently improve the knowledge on utopian discourses and practices as well as lead a semiotic analysis of the culture.